Digital Product Perception and User Satisfaction Relationship: Can They Create Feedback Intention? - Kencanasari, Retna Ayu Mustikarini; Dhewanto, Wawan; Rustiadi, Sonny (School of Business and Management Institut Teknologi Bandung, 2021)
Agile product development principles emphasize user collaboration and continuous improvement. It sometimes bothers users if they have less time, commitment and knowledge to become involved in the lengthy process of product development. Giving online feedback could be another way of contributing to product improvement. However, not all users are willing to leave reviews on online platforms. This study attempts to uncover the factors behind user feedback intention and the relationship between user roles in an agile approach. The questionnaire was completed by 113 respondents from all over Indonesia who have knowledge and experience in using digital products. The data was processed further by applying the PLS-SEM technique using the SmartPLS 3 application. The proposed model supported the positive influence of product perception on user satisfaction, and user satisfaction’s positive impact on feedback intention. Product perception is the first-order construct of attitude and perceived usefulness; meanwhile, perceived quality is influenced by product perception. This study's theoretical contribution sheds light on the relationship between user satisfaction, perception and feedback intention. Moreover, it provides practitioners practical implications towards understanding how to gather user feedback to support the initial idea in product improvement using an agile approach.